Organ donation campaign: An experience report - Medeiros, Samantha Sartore Duque Estrada; Fortuna, Fernanda de Brito; Barbosa, Gabriela Acurcio; Reis, Maria Isabel Barêa Fávero; Onório, Beatriz de Oliveira; Borges, Beatriz Carvalho; Evangelista, Beatriz Ventura; Martins, Pâmella Hellen Sousa; Wittmann, Bárbara Zantut; Lorencetti, Rafaella Gusman; Bezerra, Ana Luisa Costa (Brazilian Journal of Transplantation, 2019)
Introduction: Organ donation represents an enormous potential to save numerous lives, but 43% of relatives of brain-dead patients still refuse donating. This is due to the grieving process and the lack of elucidation on the subject, which negatively impact on the number of donors and increases the waiting lines. Therefore, it is essential to raise awareness among the population on the importance of organ donation. Purpose: To report the experience of the Organ Donation Campaign as an important innovating and transforming method to raise awareness among the population and encourage organ donation. Methods: This is a descriptive study aiming to report the experience of undergraduate medical students of PUC-Campinas University during organization and participation of Organ Donation Campaign. Results: The PUC-Campinas Committee of International Federation of Medical Students Association of Brazil (IFMSA Brazil), in partnership with Organ Procurement Organization and Parque Dom Pedro Shopping organized on May 19, 2018, the campaign in the food court of the Shopping Center in Campinas. Medical students who volunteered to participate were offered training through testimonials and multidisciplinary lecture. The public was approached individually and dynamically through by delivering records simulating the number of patients on the Brazilian Transplant Waiting List. Thus, we attempted to induce curiosity about the subject, clarify doubts and inform about the possibility of declaring themselves organ donors by encouraging dialogue with family members on the topic. As feedback, the public reported whether they had already talked about the issue with their families and whether the campaign had aroused their desire to become organ donors. Of 422 people approached, just over a third (35.3%) had never discussed organ donation, and after the event, almost all (94.5%) expressed desire to be a donor. Among 25 volunteers, none had participated in activities on the subject and 24 considered themselves able to guide others after the training. Conclusion: The Campaign promoted awareness among the general public and academics, besides of encouraging the dialogue in order to avoid that preventable constraints such as the lack of information or comprehension of the subject to hinder the advance of organ donations, which have a significant demand.